PENGARUH KINERJA KEUANGAN DAN TINGKAT INFLASI TERHADAP HARGA SAHAM PERUSAHAAN JASA TRANSPORTASI DI BURSA EFEK INDONESIA - Ni Made Riani (Forum Manajemen STIMI Handayani Denpasar, 2018)
The purpose of research to determine the influence of internal factors namely financial performance and external factors in the form of inflation rate to stock prices of transportation service companies in Indonesia Stock Exchange 2014-2016. Determination of sample using purposive sampling technique. The analytical technique used is multiple linear regression analysis, done after the free model of classical assumption symptoms are: multicolinearity, autocorrelation and heteroscedasticity. Based on the simultaneous test, the financial performance represented by current ratio variabel, debt to equity ratio, economic profitability, price earning ratio and external factor represented by the inflation rate significantly influence the stock price of transportation service company in Indonesia Stock Exchange in 2014- 2016 with a contribution of 85.2%. Through partial test, it is found that from the five independent variabels only the current ratio and economic rentability have a significant effect on the stock price, while the debt to equity ratio, the price earning ratio and the inflation rate have no significant effect on the stock price. From the analysis result concluded that current ratio and economic rentability dominant influence to share price of transportation service company which go public in Bursa Efek Indonesia. Therefore, suggestions that can be given from this research is that investors and potential investors pay more attention to current ratio and economic profitability as the basis of consideration in assessing stock prices.